Hau Rongo: the Breath of Rongo - Luke, Bobby (Auckland University of Technology, 2016)
This project is underpinned by a Taranaki genealogical worldview informing a series of knowledge exchanges that establishes the concept of ‘Ora ki te Whakatupua’, ‘sustaining life knowledge anew’. From a cosmological Taranaki perspective, this project explores an understanding of ‘Rongo’ (Deity). This visual photographic, video making and performance interdisciplinary project draws on the formation and transmission of knowledge. It particularly focuses on the knowledge of Rongo through ‘Hau Huri Matauranga’, a circular turning of knowledge, established and re-established for the future in a contemporary world. It visually examines how this worldview of Rongo influences Tikanga, specifically through concepts of Tapu and Noa and cosmological knowledge, and how this is formulated, communicated and activated. These concepts are embodied in a contemporary practice focusing on domesticity and its materiality. A contemporary 21st-century Maori material cultural forms as expressed in the home and Marae is the overarching context of this research, in which the methods become concepts, and concepts become methods
Keywords: Māori; Matauranga; Taranaki; Rongo; Tapu; Noa; Photographic study; Visual art; Tikanga; Video making; Moving image; Domestic spaces; Knowledge transmissions; Home; Marae; Ngati Ruanui; Hamua; Hapotiki; Paimarire; Parihaka; Culture; New Zealand; Landscape; Indigenous; Worldviews; Māori worldviews; Art practice; Art and design